2021
DOI: 10.3390/f12060687
|View full text |Cite
|
Sign up to set email alerts
|

Microsites Influence the Light Response of Young Douglas-Fir (Pseudotsuga menziesii (Mirb.) Franco)

Abstract: Two comparable sites with uneven-aged mixed forest stands with more than 20% Douglas-fir in the growing stock at an altitude of 650 m a.s.l. were selected. The physiological response of young trees to different light intensities was measured during the main growing season in three consecutive years, and four different light categories, which were determined from hemispherical photographs. The four light intensity categories were defined according to Indirect Site Factor (ISF%): in the open (A-ISF > 35%), at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…European experience indicates that Douglas-fir can grow on a range of soil types apart from heavy soils with pseudogley close to the surface, on dry or heavily waterlogged soils where rooting is restricted, leading to instability, and on calcareous soils. It grows best on deep, well-aerated, moderately acidic (pH 5 − 6), free draining soils of loamy-sand or sandy-loam texture which allow good root development (Rameau et al 1989;Horgan et al 2003;Perić et al 2011;Spellmann et al 2015;Novák et al 2018;Eckhart et al 2019;Čater 2021).…”
Section: Site and Climatementioning
confidence: 99%
“…European experience indicates that Douglas-fir can grow on a range of soil types apart from heavy soils with pseudogley close to the surface, on dry or heavily waterlogged soils where rooting is restricted, leading to instability, and on calcareous soils. It grows best on deep, well-aerated, moderately acidic (pH 5 − 6), free draining soils of loamy-sand or sandy-loam texture which allow good root development (Rameau et al 1989;Horgan et al 2003;Perić et al 2011;Spellmann et al 2015;Novák et al 2018;Eckhart et al 2019;Čater 2021).…”
Section: Site and Climatementioning
confidence: 99%
“…The climate sensitivity analysis of European beech (Fagus sylvatica) along an elevation gradient (110-1230 m) in south-western Germany showed that tree growth of F. sylvatica was strongly limited by low precipitation at lower elevations (110-300 m), but by low summer temperature at higher elevations (1230 m) [57]. In addition, different microsite environments and topographic conditions, such as soil microbes, soil depth and slope orientation, may also influence the sensitivity of tree growth [59][60][61]. At microsites with high moisture storage capacity, Douglas-fir (Pseudotsuga menziesii) in Slovenia favored the exposed and dry sites for optimal survival and development [61].…”
Section: Previous Growing Season Temperature Reconstructionmentioning
confidence: 99%
“…In addition, different microsite environments and topographic conditions, such as soil microbes, soil depth and slope orientation, may also influence the sensitivity of tree growth [59][60][61]. At microsites with high moisture storage capacity, Douglas-fir (Pseudotsuga menziesii) in Slovenia favored the exposed and dry sites for optimal survival and development [61]. Zhao et al [60] pointed that T. longibracteata located at a southeast-oriented hillside with a steep slope and shallow soil may experience severe water stress in summer due to having a low soil water-holding capacity and experiencing enhanced soil evaporation, while T. longibracteata growing on a northwest-oriented hillside with a flat slope and thick soil layer may be less water-restricted in summer due to a high soil water-holding capacity and experiencing low soil evaporation.…”
Section: Previous Growing Season Temperature Reconstructionmentioning
confidence: 99%